Safety of treatment regimens in multiple drug resistant tuberculosis patients compiled as per the new WHO recommendations as of 2019 - Ivanova, D. A.; Borisov, S. E.; Rodina, O. V.; Filippov, A. V.; Ivanushkina, T. N.; Litvinova, N. V. (Tuberkulëz i bolezni lëgkikh, 2020)
The objective : safety assessment of chemotherapy regimens compiled in accordance with the recommendations of World Health Organization (WHO), 2019, in patients with multiple drug resistant tuberculosis (MDR) in clinical practice settings. Subjects : Frequency, patterns, severity and risk factors of adverse events (AE) of chemotherapy regimens compiled in accordance with the WHO recommendations as of 2019 were analyzed in 122 patients with MDR and XDR respiratory tuberculosis within programmatic use of new anti-tuberculosis drugs. Results . The frequency of AE made 64.8% (95% CI 55.9-72.7%), gastrointestinal, cardiovascular and allergic events prevailed, the comorbidity was the risk factor of AE development (OR 6.44; 95% CI 1.91-21.76). AEs of with severity degrees 3-4 were observed in 24.6% (95% CI 17.8-33.0%), neurotoxic, ototoxic and hepatotoxic reactions prevailed; risk factors included female sex (OR 3.15, 95% CI 1.32-7.53) and complications of chemotherapy in the past (OR 3.50%, 95% CI 1.49-8.70). At least one anti-tuberculosis drug was canceled due to AE in 26.2% (95% CI 19.2-34.7%), and any of Group A drugs was canceled during the first 6 months of chemotherapy in 13.9% (95% CI 8.8-21.3%) of patients.